OʻZBEKISTON SHAROITIDA BOSHLANGʻICH SINF OʻQUVCHILARINI TIMSS XALQARO BAHOLASH DASTURIGA TAYYORLASH (Conferencea, 2022)
This article is about the importance of TIMSS testing system in the innovational education. The reason of intending to this test in the educational sector of the Republic of Uzbekistan. It is targetted for 2023 year. Our country will attend to this test for the first time. So that, we should prepare hardly for this system. Because the developed countries have great indicators on the international projects. We also use the education system of the Republic of Korean as a modern system. Surely, we should achieve best results on international projects.